Feasibility of optoacoustic visualization of high-intensity focused ultrasound-induced thermal lesions in live tissue - Chitnis, Parag V. (Society of Photo-Optical Instrumentation Engineers, 2010)
A 3-D optoacoustic imaging system was used to visualize thermal lesions produced in vivo using high-intensity focused ultrasound (HIFU). A 7.5-MHz, surgical, focused transducer with a radius of curvature of 35 mm and an aperture diameter of 23 mm was used to generate HIFU. A pulsed laser, which could operate at 755 nm and 1064 nm, was used to illuminate excised tissue and mice using a bifurcated fiber bundle resulting in two wide beams of light. Tomographic images were obtained while the specimens were rotated within a sphere outlined by a concave arc-shaped array of 64 piezo-composite transducers. These images were then combined to reconstruct 3-D volume images (voxel resolution 0.5 mm), which were acquired before and after HIFU exposure. In vivo optoacoustic images acquired at 1064 nm provided visualization of HIFU lesions. The lesion was indicated by a negative optoacoustic contrast. The molecular nature of such contrast may possibly be associated with reduction of the optical absorption due to reduced concentration of blood, tissue dehydration, denaturation of proteins and porphyrins, and reduction of thermoacoustic efficiency in the thermally treated tissue. These preliminary results demonstrate the potential of optoacoustic imaging to assess and monitor the progress of HIFU therapy.